Urgensi Penggunaan Big Data Analytics Dalam Audit Sektor Publik - Dharma, Adi; Hendri, Nedi (Universitas Muhammadiyah Metro, 2022)
The rapid transformation of information technology in Accounting Information System has resulted a global change in financial and non-financial data. The use of large amount of data, broad data source, and a new characteristics of data has encouraged auditors to meet the best Strategy in order to improve the quality of public audit. The aims to analyze the implementation of Big Data Analytics in the Public Sector. The objective of the study is inspired based on recent innovations in the Supreme Audit Institutions in the several countries such as Australia, USA, India and Indonesia. The method used in this research study is SWOT Analysis. Author describe the implementation of big data analytics from four perspectives which are strength, weaknesses, opportunities and threats. By using this SWOT Analysis, author can compare each aspect that led to a conclusion thatb shows the correlation between the use of Big Data Analytics in the Supreme Audit Institutions and the key transformation to success. This study makes contribution for practitioners in public sector audit to build a foundation of big data analytic in their own institutions. While in the academic areas, the result of this study can be a reference for the development of big data.